2012
DOI: 10.3892/or.2012.2091
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin enhances the response of non-Hodgkin’s lymphoma cells to ionizing radiation through further induction of cell cycle arrest at the G2/M phase and inhibition of mTOR phosphorylation

Abstract: Abstract. It is crucial to enhance tumor radiosensitivity for the purpose of both lowering the dose of ionizing radiation (IR) and achieving higher antitumor efficacy. We identified curcumin as a radiosensitizer to enhance non-Hodgkin's lymphoma (NHL) cell response to IR in vitro and further investigated the mechanism mediating this effect. We treated Namalwa, Ramos and Raji cell lines with vehicle, curcumin, IR and curcumin-IR. Cell viability and cell cycle distribution were determined to ascertain the radios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 40 publications
4
24
0
Order By: Relevance
“…Whether curcumin affected the post-translational modifications, such as phosphorylation, acetylation and ubiquitination, of either p53 or FOXO3a, thereby regulating their subcellular localization and transcriptional activities require further study. Consistent with this, other studies also found the link of curcumin and p53 or FOXO3a expression, and demonstrated the role of these transcription factors in mediating the effect of curcumin on controlling cell proliferation and other functions in other cell systems (27,28). We reasoned that more studies are required to explore the precise mechanism of p53 and FOXO3a expression, regulation and downstream pathways in mediating the overall response of curcumin.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Whether curcumin affected the post-translational modifications, such as phosphorylation, acetylation and ubiquitination, of either p53 or FOXO3a, thereby regulating their subcellular localization and transcriptional activities require further study. Consistent with this, other studies also found the link of curcumin and p53 or FOXO3a expression, and demonstrated the role of these transcription factors in mediating the effect of curcumin on controlling cell proliferation and other functions in other cell systems (27,28). We reasoned that more studies are required to explore the precise mechanism of p53 and FOXO3a expression, regulation and downstream pathways in mediating the overall response of curcumin.…”
Section: Discussionsupporting
confidence: 74%
“…The p53 and FOXO3a formed part of regulation transcriptional network to control cancer cell growth and apoptosis (33,34). In addition, curcumin induced expression of p53 or/and FOXO3a in inhibition of cancer cell growth and other functions have been shown in other cell systems (27,28,35,36). However, whether curcumin affects the interaction of these proteins to facilitate the inhibitory effect of NPC growth remain to be determined.…”
Section: Discussionmentioning
confidence: 86%
“…Reverse transcription was performed using the M‐MLV reverse transcription reagent kit (Invitrogen, Carlsbad, CA, USA). Quantitative analyses of the mRNA expression levels of PERK and eIF2α were performed using the TaqMan analysis system (Applied Biosystems, Carlsbad, CA, USA) …”
Section: Methodsmentioning
confidence: 99%
“…63 It appears to do so by generating reactive oxygen species that upregulate repressors of Sp proteins ZBTB10 and ZBTB4 and downregulation of the microRNAs mir-20a, mir-27a, and mir-17-5p, which are regulators of these Sp repressors. Interestingly, curcumin is also showing promise as a sensitizing agent to ionizing radiation in Burkitt’s type lymphoma and non-Hodgkin lymphoma 64,65 and alone in its ability to reduce expression of multiple IAPs critical to chemoresistance in pancreatic cancer cell lines. 66 The natural agents resveratrol and quercetin in combination (RQ) have also shown a similar downregulation of Sp proteins and their targets, including surviving.…”
Section: Natural Agent Transcription Modulatorsmentioning
confidence: 99%